Natural convection of CNT water-based nanofluids in a differentially heated square cavity - Estelle, Patrice; Mahian, Omid; Mare, Thierry; Öztop, Hakan Fehmi (Springer, 2017)
The present paper deals with the prediction of average Nusselt number in a differentially heated square cavity filled with Newtonian and non-Newtonian CNT nanofluids. Based on thermophysical properties which were experimentally evaluated, available correlations are used for estimating the Nusselt number and heat transfer coefficient of natural convection of CNT nanofluids with volume fractions in a range of 0.0055-0.418%. The effects of surfactant, average temperature of nanofluids within the cavity, driving temperature of cavity walls on Nusselt number are investigated and discussed. A peculiar attention is devoted to the non-Newtonian nature of CNT nanofluids in the analysis. It is found in particular that Nusselt number of nanofluids is lowered by nanoparticle content increase related to non-Newtonian behavior of nanofluids and temperature increase.
Keywords: CNT nanofluid; Natural convection; Cavity; Volume fraction influence; Non-Newtonian effect